2021
DOI: 10.3390/jcm10163728
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Prognostic Value of Ki-67 and Programmed Cell Death Ligand-1 in Patients with Upper Tract Urothelial Carcinoma

Abstract: We retrospectively enrolled 102 patients with upper tract urothelial carcinoma (UTUC) who underwent radical nephroureterectomy to examine the prognostic value of Ki-67 and programmed cell death ligand-1 (PD-L1). Then, we performed PD-L1 and Ki-67 immunohistochemical staining on whole tissue sections. The cut-off value of PD-L1 positivity was a combined positive score (CPS) ≥10 and the Ki-67 overexpression was 20%. Among the 102 patients, 16.7% and 48.0% showed positive PD-L1 expression and Ki-67 overexpression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
3
5
0
Order By: Relevance
“…This independent prognostic value of PD-L1 and PD-1 expression stand in multivariable analyses, even after adjusting for the alternative expression of PD-1 and PD-L1, respectively. Our findings are in line with those from previous reports also showing that PD-L1 [16,18,19,[25][26][27] or PD-1 [9,16,22] expression could be associated with decreased RFS, CSS and OS. Nonetheless, other reports did not find any prognostic value of PD-L1 or PD-1 expression [17,24,26,28], while the largest study to date suggested that PDL-1 expression was associated with prolonged RFS and OS but only in patients with organ-confined disease [9].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This independent prognostic value of PD-L1 and PD-1 expression stand in multivariable analyses, even after adjusting for the alternative expression of PD-1 and PD-L1, respectively. Our findings are in line with those from previous reports also showing that PD-L1 [16,18,19,[25][26][27] or PD-1 [9,16,22] expression could be associated with decreased RFS, CSS and OS. Nonetheless, other reports did not find any prognostic value of PD-L1 or PD-1 expression [17,24,26,28], while the largest study to date suggested that PDL-1 expression was associated with prolonged RFS and OS but only in patients with organ-confined disease [9].…”
Section: Discussionsupporting
confidence: 93%
“…It is noteworthy that the rate of PD‐L1 expression on tumour cells of 22.3% observed in our study fell into the range reported in the literature varying from 16.7% to 29.7% [7–9,16–20], when excluding an outlier study suggesting PD‐L1 expression in up to 55% of patients with UTUC [21]. Although we found that only 32.2% of included patients expressed PD‐1 on TILs, this was close to the range reported in the literature varying from 37.2% to 57% [7,9,22].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…According to our previous studies and others, TP53 immunostaining was considered positive, when >10% of tumor cells were stained with a strong overexpression of TP53 [19][20][21][22]. The Ki-67 labeling index (Ki-67 LI) was scored as Ki-67 LI ≥20% or Ki-67 LI <20% [23,24]. The evaluation of HER2, EGFR, FGFR, and PD-L1 was described previously [22].…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…Ki-67 is an immunostaining marker of nuclear cell proliferation, which is frequently expressed in several malignancies, such as breast, colon, and ovarian cancers ( 33 , 34 ). Referring to relevant literature, we defined that Ki-67 overexpression was 20% ( 33 35 ). In our study, 43.2% of the patients showed Ki-67 overexpression, which is consistent with the percentage of Ki-67 ≥20% in previous studies ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%